Online Based Innovative Education (VOA Learning English) to Build English Students’ Listening Skills - Alisa Hayati; Muhamad Sofian Hadi; Lidiyatul Izzah (Scripta : English Department Journal, 2022)
The previous research identified students’ listening and using the media is a way to enhance it, one of the media is the VOA Learning English website. The objective of the study is to find out and explain VOA learning English website as media can build English student listening skills. This study used quantitative research in this investigation. Moreover, this study used a pre-experimental design employed in the investigation. Based on quantitative research techniques, the writer was given the correlation between independent factors and population-dependent variables in this study. Pre-experimental design. The research was conducted at SMA PGRI 117 Tangerang. The pre-test and post-test scores revealed significant (2-tailed) findings of 0.077 a (0.05), where the significance score was higher than 0.05, based on the calculation table data normality. It indicates that the pre-test and post-test data are both normal. As a result, the data used in this study are normal, allowing for a smooth transition to the subsequent statistical test. Based on the statistical calculation, there is a positive influence between teaching listening skills by VOA Learning English website and without VOA Learning English website. The result shows that the value of the tscore (15.412) is higher than the ttable (1.714) at the significance degree of 5%. Thus that the Hypothesis (H1) is rejected and the Alternative Hypothesis (H0) is accepted. Hence, VOA Learning English website can build English students’ listening skills of class tenth-grade students of SMA PGRI 117 Tangerang.